Etnografska raziskava na pedagoškem področju - Štemberger, Tina (Revija za elementarno izobraževanje, 2017)
In the field of educational research, ethnography is not well known and consequently it is not frequently used. The concept of ethnographic research is differently, unevenly defined. It is frequently misinterpreted as qualitative research, participatory observation or as a case study. The aim of the present paper was to present ethnographic research as an approach in educational research. We first highlight the problems regarding its definition; we then present the particularities and the process of ethnographic research. We also point out to some disadvantages of this approach and we conclude the paper with the question of the role of ethnographic research in the field of education.
Keywords: ethnography; vzgoja in izobraževanje; etnografsko raziskovanje; qualitative research; quantitative research; raziskave; research process; eklektični pristop; eclectic approach; education